Linguo-Psychological Characteristics of Developing Spoken English Competence Among Academic Lyceum Students - Qobiljon Valiev (Jurnal Bahasa Daerah Indonesia, 2025)
This article explores the linguo-psychological aspects involved in enhancing spoken English competence among academic lyceum students. It investigates the influence of cognitive, affective, and psychological factors on language acquisition and the development of communicative competence in a foreign language context. Drawing from empirical classroom observations, teacher interviews, and student surveys, this research identifies effective methods that align with learners' psychological profiles to improve their oral performance in English. This article highlights the importance of motivation, self-confidence, anxiety levels, and learning strategies in shaping learners' speaking abilities